An Overview of Genetic Biomarkers Influencing Drug Response and Efficacy in Specific Populations (Journal of Advances and Scholarly Researches in Allied Education, 2024)
Genetic biomarkers are pivotal in determining drug metabolism, efficacy, and toxicity. These biomarkers include variations in genes encoding enzymes, transporters, and drug targets that modulate pharmacokinetics and pharmacodynamics. This paper explores the role of genetic biomarkers in diverse populations, emphasizing their clinical relevance and integration into personalized medicine. We also examine population-specific genetic variations and their implications for reducing healthcare disparities.